ASPEK ASPEK BUDAYA DALAM NOVEL AYAT-AYAT CINTA KARYA HABIBURRAHMAN El SHIRAZY - Rosmiyati, Ana (Acintya, 2009)
The novel entitled Ayat-ayat Cinta is a very good novel with complete contents. It is not only a literature and love novel but also a novel ofpolitics, culture, religion,flkih (laws), ethics, language, and dakwah. The interesting problem which can be raised is the complex culture in Ayat-Ayat Cinta. This research uses qualitative descriptive method and librarial study. The sources used in this research include documents containing data about things or variables covering notes, transcript, books, newspapers, etc. Social background of the novel is described by an Indonesian student who is studying in Cairn, Egypt, with the various norms and traditions. There are two social backgrounds in the novel including local social cultural background covering east and west culture and social cultural background of each characters that is east culture. Keywords: religious novel, cultural aspects, text